The Analysis of The Verdict Against Perpetrators of Criminal Acts of Narcotics in the State Court Sungguminasa - Indah Fajarwati; Jayadi, Ahkam (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Drug crime is a serious threat with far-reaching repercussions, mainly due to its transnational nature. Indonesia, including one of the countries famous for the circulation of narcotics, is not only a target but also a transit area for perpetrators of this crime before reaching the final destination. Narcotic abuse is not a legitimate and often uncontrollable behavior, but rather is carried out in order to obtain disordered psychotropic effects. As a result, it not only damages physical and mental health, but also has serious social repercussions. Therefore, the handling of drug crime is an important priority in order to maintain the safety and welfare of the community.